2003
DOI: 10.1097/00006982-200310000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Management of Giant Retinal Tears With Vitrectomy, Internal Tamponade, and Peripheral 360° Retinal Photocoagulation

Abstract: The success rate of management of GRTs with vitrectomy, internal tamponade, and peripheral 360 degrees photocoagulation of the retina without scleral buckle is high. Photocoagulation of the peripheral retina over 360 degrees appears to decrease the risk of secondary peripheral retinal tears.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
21

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 13 publications
3
59
0
21
Order By: Relevance
“…These mostly non-myopic eyes without spontaneous development of PVD in a large proportion do not usually display typical retinal degeneration predisposing to retinal breaks and carry a very low risk of developing RRD without a preceding intraocular intervention. As a consequence, a thorough vitrectomy not only around the breaks, visible degeneration and the sclerotomies, but all the way to the periphery around the whole circumference [26], prophylactic treatment of degenerative areas in attached retina [7], the use of trocar microcannular systems to reduce traction on the vitreous base during change of instruments [8] or 360°p eripheral photocoagulation [2] might be possible ways to further improve the anatomical results of PPPV for RRD.…”
Section: Discussionmentioning
confidence: 99%
“…These mostly non-myopic eyes without spontaneous development of PVD in a large proportion do not usually display typical retinal degeneration predisposing to retinal breaks and carry a very low risk of developing RRD without a preceding intraocular intervention. As a consequence, a thorough vitrectomy not only around the breaks, visible degeneration and the sclerotomies, but all the way to the periphery around the whole circumference [26], prophylactic treatment of degenerative areas in attached retina [7], the use of trocar microcannular systems to reduce traction on the vitreous base during change of instruments [8] or 360°p eripheral photocoagulation [2] might be possible ways to further improve the anatomical results of PPPV for RRD.…”
Section: Discussionmentioning
confidence: 99%
“…11 Rofail and colleagues 7 reported that the rate of postoperative complications after perfluoro-n-octane postoperative tamponade was equivalent to that after intraoperative perfluoro-n-octane. 12,13 Thus, perfluoro-n-octane appears to be effective and safe as a postoperative tamponade as long as it is used for only a short period.…”
Section: Postoperative Perfluoro-n-octane Tamponade Wasmentioning
confidence: 99%
“…We generally do not extend the photocoagulation 3601 around the normal retina, which has been recommended by several authors, to increase retinal adherence and reduce failures. 15 Over the past 15 years, the surgical technique at SNEC had evolved, with a tendency to encircle the eye less frequently, a greater usage of long-acting gases instead of silicone oil, and lens-sparing surgery, unless the GRT was too extensive.…”
mentioning
confidence: 99%